Control of vortex structures of abnormally viscous fluids in the channels of the extrusion die - Nosko, Sergey; Ahaiev, Ihor (Technology audit and production reserves, 2017)
The object of research is the vortex structures arising during the flow of anomalously viscous media in the channels of the forming equipment. One of the most problematic places is insufficient knowledge of the processes of origin and development of circulation flows. This is due to the fact that the hydrodynamic mechanisms of these processes are not completely understood. The reason for this is the lack of precise analytical solutions that allow describing the process model and choose the method of hydrodynamic control of vortex structures and on its basis to improve shaping equipment. In the course of the research it is established that the most effective way to control the hydrodynamic flow characteristics in the region of the sharp narrowing of the channel is supplying additional fluid flow in the radial direction with respect to the main flow. The design of a extrusion die is developed, which allows to realize the mixing mode of components with improved technological and energy indicators. This is due to the fact that the proposed method for controlling vortex structures has a number of distinctive features, in particular, the extruded medium passes through the die channels in the form of a sudden constriction, and then along the course of the flow, cone expansion. The mixed technological component is fed radially into the region of the vortex structures with a reduced pressure zone. Due to this, it is possible to disrupt the vortex structures, turbulence of the flow and intensive mixing of the main and additional flows. In comparison with similar known equipment, the location of mixing devices and stationary turbulators is not provided in the die channels, which reduces the energy consumption for the extrusion process. In addition, it is possible to use a lower power pump to feed the process component to the base stream. The developed device for the input of technological components into the extruded material is designed by the patent of Ukraine No. 201503942.